ANALISIS SISTEM PENERIMAAN PAJAK BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN SETELAH PENGALIHAN MENJADI PAJAK DAERAH PADA DINAS PENDAPATAN KOTA PONTIANAK - B41111042, yudo Ari Wardana B41111042 yudo (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
YUDO ARI WARDANA B41111042 ABSTRACT This research purposed to know the effectiveness BPHTB tax income, BPHTB tax contribution to local tax, and what factors that affect the local tax income. Descriptive method is the research compiled to give systematic about the information that come from subject and object of the research. Descriptive research focusing to the systematicaly explanation about the fact which came from researching. The type of data that used in the research is the secondary data in from of local income statement in 4 yearsÂ  period from 2011 â€“ 2014 which is obtained from Dinas Pendapatan Daerah Kota Pontianak and the result of the research before. The result of the research is the effectiveness ratio BPHTB income tax on 2011 is 137,68%, on 2012 is 106,22%, on 2013 is 102,71% and on 2014 107,94%, BPHTB contribution tax ratio to local tax on 2011 is 38,10%, on 2012 is 37,54%, on 2013 is 32,16%, and on 2014 is 31,13%, the factors that affect BPHTB income tax ratio potential 2011 is 31,22%, on 2012 is 35,57%, on 2013 is 31,53%, and 2014 is 27,40% collectible ratio on 2011 is 38,10%, on 2012 in 37,54%, on 2013 is 32,16%, and on 2014 is 31,13%, and arrears ratio on 2011 is -37,68%, on 2012 is -6,22%, on 2013 is -2,71%, and on 2014 is -7,94%.